Leaf area index retrieval of urban vegetation based on sentinel-2 data in Zhongshan, South China - Cai, Jiannan; Jiang, Qiancai; Shi, Yafei; Wang, Jiabin (Bangladesh Journal of Botany, 2020)
Leaf area index (LAI) is an important indicator of vegetation growth and health monitoring. The free access of Sentinel-2 optical satellite data from European Space Agency (ESA) since June 2015 made it possible to determine dynamic monitoring of LAI in a large area and a short re-entry period, owing to its high spatial resolution (up to 10 m) and unique band combination. These features of Sentinel-2 may bring great application potential in urban forestry management and ecological environment monitoring. In case of Zhongshan city in Guangdong Province, based on Sentinels Application Platform (SNAP) software and two scenes of Sentinel-2 data, LAI of the whole city, as well as specific areas, were retrieved and analyzed. The retrieval result was consistent with the ecological spatial pattern and the vegetation protection status in Zhongshan city, also highly consistent with the field LAI measurement in the forest in a reservoir. The result indicates that this method has good applicability and accuracy in urban LAI inversion.